2006
DOI: 10.1007/11872153_21
|View full text |Cite
|
Sign up to set email alerts
|

ARSM: Auto Rate Selection Multicast Mechanism for Multi-rate Wireless LANs

Abstract: Multicast is an efficient paradigm for transmitting data from a sender to a group of receivers. The IEEE 802.11 wireless LANs standards specify how to send multicast frames with no ACK and using one of the Basic Service Set (BSS) rates. This situation has led many researchers to design techniques aiming to improve reliability of a multicasting mechanism. The Leader-Base Protocol (LBP) is one such mechanism proposed in the literature that is the most promising approach. The main idea behind the design of the LB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…In [8], Villalon et al have proposed an auto-rate selection mechanism for multicasting (ARSM). ARSM dynamically selects a multicast rate based on the feedback information pertaining to channel conditions perceived by mobile stations.…”
Section: Related Workmentioning
confidence: 99%
“…In [8], Villalon et al have proposed an auto-rate selection mechanism for multicasting (ARSM). ARSM dynamically selects a multicast rate based on the feedback information pertaining to channel conditions perceived by mobile stations.…”
Section: Related Workmentioning
confidence: 99%
“…먼저, 멀티캐스트 서비스에 신뢰성을 제공함과 동시에 전 송 속도 적응 기법을 적용시키기 위한 연구들이 진행되었다 [1][2][3] 채널 상태가 가장 좋지 않은 노드의 채널 환경에 적합한 전 송 속도를 사용한다 [3]. H-ARSM의 경우, 향상 계층을 기본 계층보다 한 단계 빠른 전송 속도를 사용하여 전송한다 [6].…”
unclassified
“…We compare the performance of EDCA with the compatible B-EDCA mechanism as access model to the channel. Concern to the multicast mechanism, in [12] we showed that the standard is unable to effectively provide multicast services, and ARSM enhance the performance of LBP and RAM mechanism. For this reason, we study ARSM and H-ARSM as method to send the multicast traffic.…”
Section: Performance Evaluationmentioning
confidence: 96%
“…For reduce this overhead, we presented in [12] a novel mechanism named Auto Rate Selection mechanism for Multicast (ARSM) in multirate wireless LAN. Basically, the ARSM mechanism dynamically selects the multicast data rate based on the channel conditions perceived by the MTs.…”
Section: Multicast Transmission Over Ieee 80211mentioning
confidence: 99%
See 1 more Smart Citation